Microwave‐Assisted Suzuki‐Miyaura Cross Coupling using Nickel as Catalyst to Rapidly Access to 3‐Arylazetidine. Issue 28 (2nd October 2017) - Dequirez, Geoffroy; Bourotte, Marilyne; Porras de Francisco, Esther; Remuiñan Blanco, Modesto J.; Déprez, Benoit; Willand, Nicolas
Abstract: The efficient synthesis of 3‐arylazetidine derivatives is reported using a Nickel‐catalyzed Suzuki‐Miyaura coupling between arylboronic acids and a N‐BOC‐protected 3‐iodoazetidine under microwave irradiation. The reaction tolerates a great range of substituents such as electrodonating and electron withdrawing groups opening the field of the diversity especially in the context of structure activity relationship studies. Abstract : Suzuki‐Miyaura coupling between arylboronic acids and protected 3‐iodoazetidine under microwave irradiation provide the rapid access to a wide range of 3‐arylazetidine derivatives. This reaction is catalyzed with Nickel catalyst and under basic conditions.